2017
DOI: 10.1017/s1431927617000150
|View full text |Cite
|
Sign up to set email alerts
|

Interface Segregation and Nitrogen Measurement in Fe–Mn–N Steel by Atom Probe Tomography

Abstract: Improved understanding of the interactions between solutes and the austenite/ferrite interface can benefit modeling of ferrite growth during austenite decomposition, as the transformation kinetic is significantly affected by solutes that influence interface mobility. Solute-interface interactions dominate solute segregation at the interface in binary systems, but in multi-component alloys, solute-solute interactions may also affect segregation. In this study, interface segregation in Fe-Mn-N is examined and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The origin of the missing nitrogen is considered to be the occurrence of neutral nitrogen (N) or nitrogen gas molecules (N 2 ) in field evaporation, which cannot be detected as signals by atom probe instruments (Langelier et al, 2017). In the Fe–N phase system, the N 2 gas phase preferably emerges under thermodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of the missing nitrogen is considered to be the occurrence of neutral nitrogen (N) or nitrogen gas molecules (N 2 ) in field evaporation, which cannot be detected as signals by atom probe instruments (Langelier et al, 2017). In the Fe–N phase system, the N 2 gas phase preferably emerges under thermodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They predicted that approximately 30% of nitrogen is obscured by the dominant peak of 56 Fe 2+ . Recently, Langelier et al (2017) analyzed Fe–Mn–N martensitic steels and found that the apparent concentration of solute nitrogen decreased when measured using pulsed laser atom probes. They predicted the formation of nitrogen gas molecules (N 2 ) and an outward diffusion of nitrogen during the fabrication of the focused ion beam (FIB) specimen, in addition to pile-up and overlapping effects.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of alloying elements on bainitic transformation behavior, there are wide variety of reports on elements such as Mn 7)-9) , Si 8) -10) , and Mo 11), 12) , main alloying elements, in the current Fe-C based TRIP steels. Although there are several reports on AF formation during denitriding experiment in Fe-Mn-N alloys 13), 14) , reports on the bainitic transformation are limited to Fe-N binary alloys with at high nitrogen concentrations 15)-17) . Therefore, the effect of alloying element additions on the bainitic transformation behavior of low-nitrogen steels comparable to commercial Fe-C TRIP steels, which are practical steels, is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…High-precision dilatometry work on the massive transformation has led to better estimates of the interface mobility [6][7][8]. Improved precision and wider availability of electron probe microanalysis (EPMA) [9,10] and atom probe tomography (APT) [11][12][13] have provided better estimates of interfacial conditions (carbon content) and solute segregation at the ferrite/austenite interface. Decarburization [14][15][16] and cyclic transformation [17][18][19] experiments have delivered accurate growth kinetic measurements by minimising the complications from nucleation.…”
Section: Introductionmentioning
confidence: 99%